DESAIN RHYTHM SECTION SEBAGAI MEDIA PEMBELAJARAN MUSIK DI SEKOLAH DASAR - Herdiyana, - (2022)
ABSTRACT This research is motivated by the lack of media adjustment in learning. This problem is caused by the lack of facilities and infrastructure that support learning the art of musik, also in carrying out the learning there are many teachers who do not understand in teaching musik learning because of limited knowledge about learning the art of musik itself. This causes learning in the classroom to be monotonous. Students tend to lack motivation and interest in following these lessons, where art learning should be a fun learning for students. Therefore, this research was carried out with the aim of describing the needs, design, placement, and application of digital-based rhythm media in the form of MP3 as a medium for learning musik in elementary schools. The research method used is the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The data obtained using interviews, observation, documentation, expert judgment, and questionnaires. The results obtained are based on 4 aspects in measuring student interest, the largest proportion of interest contained in the very high category. In the aspect of feeling happy students get the percentage results of 85%, aspects of student interest 60%, student attention 75% and aspects of involvement by 85%. In the high category, the results obtained 13% on aspects of feeling happy, aspects of student interest 35%, aspects of student attention 25%, and aspects of student involvement 15%. In the medium category, the results obtained 2% from the aspect of student pleasure, 5% from the aspect of student interest, 0% from the aspect of student attention and involvement. So, based on the results of the description, it can be concluded that the digital-based rhythm section media in the form of MP3 has a significant influence on students' interest in learning the art of musik. Keywords: Rhythm Section Design, Learning Media, Musik Learning, Interests, Elementary School